Sociopolitical, mental health, and sociodemographic correlates of COVID-19 vaccine hesitancy among young adults in 6 US metropolitan areas - Katharina E. Klinkhammer; Katelyn F. Romm; Deanna Kerrigan; Karen A. McDonnell; Amita Vyas; Yan Wang; Yan Ma; Carla J. Berg (Preventive Medicine Reports, 2022)
Given the need to increase COVID-19 vaccine uptake among US young adults, we examined the extent of COVID-19 vaccine hesitancy in this population and related factors. We analyzed Fall 2020 survey data from 2,453 young adults (ages 18–34) across 6 US metropolitan statistical areas (MSAs; Meanage = 24.67; 55.8% female; 5.4% Black, 12.7% Asian, 11.1% Hispanic; 75.5% college degree or higher). Multivariable linear regression examined correlates of COVID-19 vaccine hesitancy (index score of willingness and likelihood of being vaccinated), including sociopolitical factors (MSA, political orientation, COVID-related news exposure), COVID-19 symptoms and testing, mental health (e.g., COVID-related stress), and sociodemographics. 45.3% were “extremely willing” to get the vaccine (19.8% very, 14.2% somewhat, 3.7% don’t know, 7.0% a little, 10.1% not at all); 40.2% were “extremely likely” to get vaccinated (22.1% very, 14.2% somewhat, 5.2% don’t know, 7.9% a little, 10.3% not at all). Greater vaccine hesitancy was significantly related to living in specific MSAs (i.e., Atlanta, Oklahoma City, San Diego, Seattle vs. Minneapolis or Boston), identifying as Republican or “no lean” (vs. Democrat), and reporting less COVID-related news exposure and less COVID-related stress, as well as identifying as older, female, Black or other race, having less (vs. greater) than a college education, being married/cohabitating, and having children in the home. Interventions to improve COVID-19 vaccine uptake among hesitant young adults should include communication that address concerns, particularly among women, minority groups, and those from certain geographic regions and/or differing political orientations, and require identifying communication channels that appeal to these groups.